2015
DOI: 10.5966/sctm.2015-0054
|View full text |Cite
|
Sign up to set email alerts
|

Drug Transporter-Mediated Protection of Cancer Stem Cells From Ionophore Antibiotics

Abstract: Ionophore antibiotics were reported to selectively kill cancer stem cells and to overcome multidrug resistance, but mechanistic studies of the significance of drug transporters for treatment with these compounds are lacking. We applied chemosensitivity testing of well-characterized human cancer cell lines to elaborate on whether drug transporters are involved in protection from the cytotoxic effects of the ionophore antibiotics salinomycin and nigericin. Our experiments demonstrated that ionophore antibiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…Thereafter, reports from Rotin and Margolis had shown that nigericin inhibited DNA synthesis of cancer cells by increasing intracellular pH and causing acidification of cytoplasm (6,7). Recently, nigericin was found to be involved in various types of cancer (8)(9)(10)(11). For example, in 2010, the study of Mashima and colleagues showed that nigericin-like compounds suppressed androgen receptor expression at the mRNA level and could be applied as new-type therapeutic agents in hormone-refractory prostate cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, reports from Rotin and Margolis had shown that nigericin inhibited DNA synthesis of cancer cells by increasing intracellular pH and causing acidification of cytoplasm (6,7). Recently, nigericin was found to be involved in various types of cancer (8)(9)(10)(11). For example, in 2010, the study of Mashima and colleagues showed that nigericin-like compounds suppressed androgen receptor expression at the mRNA level and could be applied as new-type therapeutic agents in hormone-refractory prostate cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…SP fractions derived from ovarian cancer cell lines exhibited marked resistance to cytotoxic agents . Our clinical data demonstrate that exclusively platinum‐refractory cancer specimens showed significantly increased Vav3.1 mRNA levels compared to all other cancers including fully platinum sensitive, PPS and even platinum resistant tumors.…”
Section: Discussionmentioning
confidence: 67%
“…SP fractions derived from ovarian cancer cell lines exhibited marked resistance to cytotoxic agents. 46,47 Our clinical data demonstrate that exclusively platinum-refractory cancer specimens showed significantly increased Vav3.1 mRNA levels compared to all other cancers including fully platinum sensitive, PPS and even platinum resistant tumors. Although, administration of platinum is generally associated with high rates of clinical responses, drug exposure can lead to an adaptive response rendering malignant cells less platinumsusceptible over time.…”
Section: Increased Vav31 Expression In Platinum-refractory Patientsmentioning
confidence: 72%
“…CSCs 33, 34, 60 and EMT 35, 37, 42, 43 both fuel cancer progression and mediate drug resistance. The transmembranous glycoprotein EpCAM exerts distinct and partially paradoxical functions in CSCs and EMT: while CSCs from epithelial‐derived tumors express high levels of EpCAM, EMT cells have downregulated the expression of this key epithelial denominator.…”
Section: Discussionmentioning
confidence: 99%